A comprehensive model for examining multi-dimensional users' trust of m-government services. (26th September 2022) - Alkhaldi, Ayman N.
Though the literature has identified that trust construct is the entrance to e-government adoption, previous studies have measured the effect of trust using general sub-dimensions, which leads to generalised results. However, trust is a wide-ranging concept and warrants conceptualisation as a multi-dimensional factor and the primary indicator of a user's perception in online transactions. Therefore, this research proposes a multi-dimensional trust model to better understand the possible determinants associated with the concept of trust in users' intention to use m-government services. This study utilised Structural equation modelling using AMOS software. The results distinguish between trust sub-dimensions and show that users trust governmental capabilities, trust information quality, and trust mobile phones capabilities can increase their intention to use m-government services, but not users' trust in the government's involvement, trust m-government systems, trust personal technical literacy; nor help desk service quality. Users trusting m-government systems can decrease their perception of risk.